(untitled) (Economics and region, 2025)
The article analyses methodological approaches to the digital transformation of the economy and universities, in particular, the role of digital technologies in the development of the educational process and management activities of higher education institutions. It is determined that digitalisation is a key factor that affects economic, social and educational processes, which allows universities to provide a high level of training in the context of globalisation and the digital economy. The article discusses in detail the areas of digital transformation of universities, including the introduction of mobile platforms, interactive technologies and distance learning, which significantly improve access to educational materials and facilitate individualised learning. The paper also examines the challenges and opportunities faced by universities in the course of digitalisation, in particular the need to adapt curricula, management processes and research activities to new requirements. It determines the importance of strategic management in the context of digital transformation, which allows universities to effectively respond to the challenges of contemporary times and ensure their sustainable development.